Russia's Energy Security Doctrine: Addressing Emerging Challenges and Opportunities - Bogoviz, Aleksei Valentinovich; Lobova, Svetlana Vladislavlevna; Ragulina, Yulia Vyacheslavovna; Alekseev, Alexander Nikolaevich (International Journal of Energy Economics and Policy, 2018)
The paper focuses on the significance of energy security in the general structure of Russia's national security. Given the importance of the fuel and energy complex in the economy of Russia, we review the main provisions of the Energy Security Doctrine of Russia, which was adopted in the year of 2012 and became one of the key strategic documents on energy in Russia that should guide all energy policies both at the federal and regional levels. Than we argue that the Doctrine is to be advanced because of the new emerging threats and challenges that Russia's energy sector is facing at the moment. We give particular importance to the development of transport and energy infrastructure in Russia and neighboring countries as a way of strengthening country's energy security. The issue of regional energy security is also discussed, including its main theoretical provisions. We demonstrate that the development of the energy dimension in the integration processes within the Eurasian Economic Union is to become one of the key priorities of a new version of the 2012 Energy Security Doctrine of Russia. Keywords: energy security, Energy Security Doctrine of Russia, Eurasian Economic Union. JEL Classifications: Q2, Q3, Q4 https://doi.org/10.32479/ijeep.6736